How successful is the Higher Institute of Energy, Kuwait, in reducing dependence on expatriates? - Al-Ali, Salah (Technium Social Sciences Journal, 2021)
The role of technical and vocational education in enhancing indigenous capabilities is highly discussed by authors, observers, and academics. In fact, there is a common understanding that technical and vocational education is a dual educational system that allow students to transfer what they have been learned in classroom, laboratories and workshops into real work environment. The success of technical and vocational education would depend on the management mentality in the ability in forging and effective and fruitful linkage with industries and business. It is a management responsibility to identify and determine the level of knowledge, skills, and attitudes that are mostly required by the recipients of technical and vocational graduates. Kuwait, as one of the gulf states, the shortage of indigenous skilled and semi-skilled manpower in noted in essential sectors of the economy (e.g., electricity and water and the oil sector). Decision makers have realized the significant role of technical and vocational institutions in providing essential sectors of the economy with the skilled and semi-skilled national manpower in order to reduce, to great extent, the dependence on expatriates. The Higher Institute of Energy, HIE, was forged by the Kuwaiti Government with the aim to equipped local manpower with the know-how and know-why that are applied in local industries. The research is focus on measuring the perception of a sample of heads of supervisors at the Ministry of Electricity and Water and at the oil sector towards the quality of HIE graduates. The research is based on extensive field work that encompasses a review of the related literature, interviews with a sample of heads of supervisors at the Ministry of Electricity and Water and at the oil sector to assess the quality of field training program and the standard of the HIE graduates. Finally, the research will argue that unless the HIE recognize and appreciate the value of building a strong linkage with local industries, its contribution in tackling the shortage of skilled and semi-skilled indigenous in essential sectors on the economy will be below the government expectations, thus continuing relaying on expatriates for years ahead.